Hubungan Dukungan Keluarga terhadap Keberhasilan Pemberian Asi Ekslusif di Wilayah Kerja Puskesmas Darussalam - Humaira Humaira; Fauziah Fauziah; Nurul Sakdah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
The percentage of newborns aged 0–6 months in Aceh Besar who received exclusive breastfeeding in 2022 was 55.9%, still far below the national target of 80%. Perception, knowledge, education, and employment are examples of various internal elements possessed by a woman that influence the effectiveness of exclusive breastfeeding to her child. Meanwhile, the mother's external environment consists of the support she receives from her partner and family members, as well as assistance she receives from medical personnel. This study aims to collect data from the Darussalam Community Health Center (Puskesmas) to draw conclusions about the correlation between family support and the success rate of exclusive breastfeeding. This study used a quantitative cross-sectional design. The study population was 82 people. This study excluded some individuals due to several challenges that arose during its implementation. The questionnaire used was the Guttman scale, which provides twenty answer options: yes or no. The chi-square test was chosen as the data analysis method. This study was conducted from April 14, 2025, to May 16, 2025. The findings indicate a correlation between the success of exclusive breastfeeding in the Darussalam Community Health Center (Puskesmas) and the practice of exclusive breastfeeding. This variable is associated with other variables such as instrumental support, emotional support, evaluation support, information support, and family support. The effectiveness of exclusive breastfeeding depends on the study site's ability to conduct relevant monitoring and evaluation, improve health and education, and encourage family involvement.